2003
DOI: 10.2514/2.1990
|View full text |Cite
|
Sign up to set email alerts
|

Noise, Turbulence, and Thrust of Subsonic Freejets from Lobed Nozzles

Abstract: A study of noise bene t, vis-à-vis thrust penalty, and its correlation to turbulence intensities is conducted for freejets issuing from lobed nozzles. Four convergent nozzles with constant exit area are used in the experiments. Three of these are of rectangular lobed con guration having 6, 10, and 14 lobes; the fourth is a circular nozzle. Increasing the number of lobes results in a progressive reduction in the turbulence intensities as well as in the overall radiated noise. The noise reduction is pronounced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 22 publications
3
5
0
1
Order By: Relevance
“…Thus, as we move further downstream from nozzle exit ( X/D j = 2.5), the velocity profile become similar to that of jet emanating from the conventional round nozzle. The same trend has already been reported by Zaman et al (2003) in their experimental work on lobed nozzles.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, as we move further downstream from nozzle exit ( X/D j = 2.5), the velocity profile become similar to that of jet emanating from the conventional round nozzle. The same trend has already been reported by Zaman et al (2003) in their experimental work on lobed nozzles.…”
Section: Resultssupporting
confidence: 88%
“…As penetration increases the small scale turbulent structures appear well in advance and hence the radial profile of these highly penetrating nozzles deviates largely from conventional nozzle. The same "w" shaped radial profile observed in the present simulations was reported by Zaman et al (2003) for jet emanating from lobed nozzles in their experimental work. As the flow proceeds downstream, the turbulence intensity reduces and as a result the velocity profile gets smoothened to a conventional mode.…”
Section: Comparison Of Mean Axial Velocity For Different Lobe Penetra...supporting
confidence: 90%
See 1 more Smart Citation
“…When a conventional splitter mixer is replaced by a lobed mixer, mixing efficiency of the mixed flow is found to be raised apparently [2]. Moreover, both the infrared signal and the aero-acoustic noise are suggested to be alleviated with the usage of a well-designed lobed mixer [3] [4]. However, due to the enhanced mixing process downstream of the lobed trailing edge, more energy losses are required for the mixing process.…”
Section: Introductionmentioning
confidence: 99%
“…Schematic of a generic lobed mixerThe enhancement in mixing in the presence of lobes is primarily attributed to the increase in interfacial area and the formation of coherent streamwise vortices[106,107].Paterson[108] performed the first detailed study of the lobed-mixer flow field and revealed the existence of the streamwise vortices that develop from radially oriented secondary flows prevailing along the sidewalls of the lobes. Werle et al[109] and Eckerle et al[110] observed the streamwise vortices to have a diameter on the order of the lobe width upon formation.…”
mentioning
confidence: 99%